I’m not half and half: navigating being a “both” in discipline-based education research - Holt, Emily A.; Sung, Rou-Jia; Lo, Stanley M. (Frontiers in Education, 2024)
Introduction and methods Through years of conversations, three discipline-based education researchers used a duoethnographic process to interrogate their own discipline-based education research (DBER) identities. We present a description of how these individuals navigate being a “both,” gathered through reflections, discussions, and deeper research to explore perspectives of our professional identities and what we perceive those identities look like to our peers, supervisors, and trainees. Results Our own definitions and eventually realized identities as a “both” emerged through this research process. We envision that science faculty have multiple roles, demands, and identities; at the most basic level, they are “both” an educator and a researcher. In the unique case of discipline-based education research (i.e., scholars studying the teaching and learning of science often in science departments), some faculty find an overlap between complementary yet sometimes competing research agendas (i.e., biology research (BR) and discipline-based education research (DBER)), of which they do “both.” Discussion This article has two key contributions. First, it articulates this side-glancing process of our navigation of being a DBER “both,” leveraging each of our unique perspectives and the literature. Second, it represents how such an exploration may be useful to other interdisciplinary researchers in understanding and embracing all parts of their identities.